A noval noninvasive targeted therapy for osteosarcoma: the combination of LIFU and ultrasound-magnetic-mediated SPIO/TP53/PLGA nanobubble - Ren, Honglei; Xiang, Shanlin; Liu, Aiguo; Wang, Qian; Zhou, Nian; Hu, Zhenming (Frontiers in Bioengineering and Biotechnology, 2024)
Purpose: Osteosarcoma (OS) is the most common type of primary malignant bone tumor. Transducing a functional TP53 gene can effectively inhibit OS cell activity. Poly lactic acid-glycolic acid (PLGA) nanobubbles (NBs) mediated by focused ultrasound (US) can introduce exogenous genes into target cells in animal models, but this technique relies on the passive free diffusion of agents across the body. The inclusion of superparamagnetic iron oxide (SPIO) in microbubbles allows for magnetic-based tissue localization. A low-intensity-focused ultrasound (LIFU) instrument was developed at our institute, and different intensities of LIFU can either disrupt the NBs (RLI-LIFU) or exert cytocidal effects on the target tissues (RHI-LIFU). Based on these data, we performed USmagnetic-mediated TP53-NB destruction and investigated its ability to inhibit OS growth when combined with LIFU both in vitro and in vivo. Methods: Several SPIO/TP53/PLGA (STP) NB variants were prepared and characterized. For the in vitro experiments, HOS and MG63 cells were randomly assigned into five treatment groups. Cell proliferation and the expression of TP53 were detected by CCK8, qRT-PCR and WB, respectively. In vivo, tumor-bearing nude mice were randomly assigned into seven treatment groups. The iron distribution of Perls' Prussian blue-stained tissue sections was determined by optical microscopy. TUNEL-DAPI was performed to examine apoptosis. TP53 expression was detected by qRT-PCR and immunohistochemistry. Results: SPIO/TP53/PLGA NBs with a particle size of approximately 200 nm were prepared successfully. For in vitro experiments, ultrasound-targeted transfection of TP53 overexpression in OS cells and efficient inhibition of OS proliferation have been demonstrated. Furthermore, in a tumorbearing nude mouse model, RLI-LIFU-magnetic-mediated SPIO/TP53/PLGA NBs increased the 3 transfection efficiency of the TP53 plasmid, resulting in apoptosis. Adding RHI-LIFU to the treatment regimen significantly increased the apoptosis of OS cells in vivo.Combining LIFU and US-magnetic-mediated SPIO/TP53/PLGA NB destruction is potentially a novel noninvasive and targeted therapy for OS.